THE EFFECT OF DEBATE STRATEGY TOWARDS STUDENTS SPEAKING ABILITY AT THE ELEVENTH GRADE STUDENTS OF MA AL URWATUL WUTSQO JOMBANG - Khudriyah Khudriyah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
English is very essential at globalization era. In today’s era, multilingualism has become more than just ‘important’. Knowing a foreign language other than native language has evolved to be extremely beneficial, so it is important to teach English as foreign language. This research is aimed to know the effect debate strategy towards students speaking ability, with quantitative approach. The result of the research is debate strategy has affected the students speaking ability of eleventh grade of MA al Urwatul Wutsqo Jombang, because based on the result of F-test the population variance is equal. Based on the result of t test is empirical t is higher that theoretical t, so the debate has affected the students speaking ability with low level, and the result of significance is 0,000 < 0, 05, there is difference speaking ability between students who are taught using debate as strategy and conventional method.